A generic self-assembly approach towards phototheranostics for NIR-II fluorescence imaging and phototherapy. (1st March 2022) - Cui, Cao; Wang, Chenlu; Fu, Qinrui; Song, Jibin; Zou, Jianhua; Li, Ling; Zhu, Jianwei; Huang, Wei; Li, Lin; Yang, Zhen; Chen, Xiaoyuan
Abstract: Controllable self-assembly of photonic molecules for precise biomedicine is highly desirable but challenging to prepare multifunctional nano-phototheranostics. Herein, we developed a generic self-assembly approach to design nano-phototheranostics that provides NIR-II fluorescence imaging and phototherapy. We first designed and synthesized two amphiphilic photonic molecules, PEG2000 -IR806 and BODIPY. Then, we prepared the co-self-assembled phototheranostic agents, PEG2000 -IR806/BODIPY nanoparticles (PIBY NPs). The morphology of the PIBY NPs is controllable by adjusting the ratio of PEG2000 -IR806 and BODIPY during self-assembly. The NIR-II fluorescence properties and phototherapy capability of the PIBY NPs were demonstrated in vitro and in vivo . By tuning the ratio of PEG2000 -IR806 and BODIPY, the PIBY NPs showed various morphologies ( e.g. spherical nanoparticles, nanovesicles and rod-like nanoparticles). The PEG2000 -IR806 plays two roles in the co-self-assemblies, one is second near-infrared (NIR-II, 1000–1700 nm) agent, the other is the surfactant for BODIPY encapsulation. The phototherapeutic PIBY NPs all show bright NIR-II fluorescence and effective phototherapeutic (photothermal and photodynamic) properties, which are attributed to IR806 and BODIPY, respectively. The driving force of the self-assembly can be attributed to the electrostatic interaction between NIR806 and BODIPY and their hydrophobicity. The rod-like PIBY NPs (rPIBY NPs) demonstrated a low half inhibitory concentration (IC50 ) of 3.96 µg/mL on U87MG cells. The NIR-II imaging showed the accumulation of rPIBY NPs in the tumor region. After systemic injection of rPIBY NPs at low dose (0.5 mg/kg), the tumor growth was greatly inhibited upon laser irradiation without noticeable side effects. This study provides a generic self-assembly approach to fabricate NIR-II imaging and phototherapeutic platform for cancer phototheranostics. Statement of significance: Nanophototheranostics providing NIR-II fluorescence imaging and phototherapy are expected to play a critical role in modern precision medicine. Controllable self-assembly of optical molecules for the fabrication of efficient nanophototheranostics is highly desirable but challenging. This work reports for the first time the co-assembly of a NIR-II imaging contrast agent and a phototherapeutic agent to yield nanophototheranostics with various morphologies. The design of molecular co-assembly with complementary optical functions can be a generic method for future the development of phototheranostics. Graphical abstract: Image, graphical abstract